A review of the applications of phase change materials in cooling, heating and power generation in different temperature ranges - Du, Kun; Calautit, John Kaiser; Wang, Zhonghua; Wu, Yupeng; Liu, Hao (Elsevier, 2018)
Latent heat thermal energy storage is an attractive technique as it can provide higher energy storage density than conventional heat energy storage systems and has the capability to store heat of fusion at a constant (or a near constant) temperature corresponding to the phase transition temperature of the phase change material (PCM). This paper provides a state-of-the-art review on phase change materials (PCMs) and their applications for heating, cooling and electricity generation according to their working temperature ranges from (−20 °C to +200 °C). Four working temperature ranges are considered in this review: (1) the low temperature range from (−20 °C to +5 °C) where the PCMs are typically used for domestic and commercial refrigeration; (2) the medium low temperature range from (+5 °C to +40 °C) where the PCMs are typically applied for heating and cooling applications in buildings; (3) the medium temperature range for solar based heating, hot water and electronic applications from (+40 °C to +80 °C); and (4) the high temperature range from (+80 °C to +200 °C) for absorption cooling, waste heat recovery and electricity generation. Different types of phase change materials applied to each temperature range are reviewed and discussed, in terms of the performance, heat transfer enhancement technique, environmental impact and economic analysis. The review shows that, energy saving of up to 12% can be achieved and a reduction of cooling load of up to 80% can be obtained by PCMs in the low to medium–low temperature range. PCM storage for heating applications can improve operation efficiency from 26% to 66%, depending on specific applications. Solar thermal direct steam generation (DSG) is the most common electricity generation application coupled with PCM storage systems in the high temperature range, due to the capability of PCMs to store and deliver energy at a given constant temperature. The recommendations for future research are also presented which provide insights about where the current research is heading and highlights the challenges that remain to be resolved.